Selenium speciation-dependent cancer radiosensitization by induction of G2/M cell cycle arrest and apoptosis - Nie, Shiqing; He, Xin; Sun, Zhiting; Zhang, Yan; Liu, Ting; Chen, Tianfeng; Zhao, Jianfu (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Radiation therapy has Q6long been a routine and effective treatment for non-small cell lung cancer (NSCLC), but the radioresistance and side effects have limited its application. In recent years, the superiority showed by trace element selenium in tumor radiotherapy sensitization has received wide attention. However, different forms of selenium compounds exhibit different chemical properties and their mechanisms of action on tumors may be different. Methods: Human non-small cell lung cancer SPC-A1 cells were studied. Drug toxicity was detected by MTT assay. The selenium content absorbed in vitro at different time points was detected by ICP-MS. Colony formation were conducted to observe the radiosensitization effect of different selenium compounds on SPC-A1 cells, and to compare the proliferation ability of SPC-A1 cells treated by radiation alone and radiation combined with different selenium compounds. Cell migration was detected by cell scratch assay. The changes of cell cycle and apoptosis were detected by flow cytometry. DCFH-DA fluorescent probe was used to detect the effects of different selenium compounds combined with X-ray on ROS production. Results: In this study, these four representative selenium compounds all have a certain ability to enhance the ability of radiotherapy to inhibit tumor cell proliferation and migration, and the mechanism may be related to blocking cell cycle in G2/M phase, activating the caspase cascade and reducing intracellular ROS levels to induce tumor cell apoptosis. Among them, -2-valent organic selenium has the most obvious effect, mainly inhibits cell migration, and induces early apoptosis by activating a large number of caspase-3, and arrest the cell cycle in S phase and G2/M phase. 0-valent selenium nanoparticles mainly arrest the cell cycle in G2/M phase. +4-valent inorganic selenium exerts its antitumor effects primarily by inhibiting tumor cell migration and inducing early apoptosis of tumor cells. Discussion: In this paper, the antitumor effects of four different forms of selenium compounds combined with X-rays on SPC-A1 cells were investigated, and their inhibitory effects on the proliferation and migration of cancer cells and their mechanisms were examined. We found that the radiosensitizing effect of selenium on NSCLC was closely related to its selenium form through the study of the sensitizing effect of different kinds of selenium compounds on radiotherapy.